Rooming-in for Infants at Risk of Neonatal Abstinence Syndrome - McKnight, Sarah; Coo, Helen; Davies, Gregory; Holmes, Belinda; Newman, Adam; Newton, Lynn; Dow, Kimberly (American Journal of Perinatology, 2016)
Objective To examine the impact of a rooming-in program for infants at risk of neonatal abstinence syndrome (NAS) on the need for pharmacologic treatment and length of hospitalization.Study Design Our hospital implemented a rooming-in program for newborns at risk of NAS in June 2013. Previously, standard care was to admit these infants to the neonatal intensive care unit. Charts were reviewed to abstract data on at-risk infants born in the 13-month periods prior and subsequent to implementation of rooming-in (n = 24 and n = 20, respectively) and the groups were compared with the outcomes of interest.Result Rooming-in was associated with a reduced need for pharmacologic treatment and shorter length of stay.Conclusion These findings add to an emerging body of evidence on the health care resource utilization benefits associated with rooming-in for infants at risk of NAS. Future studies should evaluate a broader range of outcomes for this model of care.
Keywords: opioids; neonatal abstinence syndrome; rooming-in; length of stay; treatment